(untitled) (Baghdad Science Journal, 2025)
The study aims to investigate the antimicrobial activity of propolis obtained from different regions of Iraq compared with that of propolis obtained from Iran. Samples were investigated for their antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa, Eschericha coli, Klebsiella pneumoniae, Bacillus cereus , Staphylococcus epidermidis and Candida albicans using standard antimicrobial assays. Marked variations in the antimicrobial activity of the different propolis samples were observed, the method of extraction selected gives the highest antimicrobial activity and the best alcohol concentration using in the extraction of propolis , then the crude extract of propolis showed synergistic effect with some antibiotics in inhibition of pathogenic microorganisms.